Low serum vitamin D status is associated with incident Alzheimer’s dementia in the oldest old - Melo van Lent, Debora; Egert, Sarah; Wolfsgruber, Steffen; Kleineidam, Luca; Weinhold, Leonie; Wagner-Thelen, Holger; Stoffel-Wagner, Birgit; Bickel, Horst; Wiese, Birgitt; Weyerer, Siegfried; Pentzek, Michael; Jessen, Frank; et al. (Nutrients, 2023)
Background. Vitamins A, D and E and beta-carotene may have a protective function for cognitive health, due to their antioxidant capacities. Methods. We analyzed data from 1334 non-demented participants (mean age 84 years) from the AgeCoDe study, a prospective multicenter-cohort of elderly general-practitioner patients in Germany, of whom n = 250 developed all-cause dementia and n = 209 developed Alzheimer’s dementia (AD) during 7 years of follow-up. We examined whether concentrations of vitamins A (retinol), D (25-hydroxycholecalciferol) and E (alpha-tocopherol) and beta-carotene, would be associated with incident (AD) dementia. Results. In our sample, 33.7% had optimum vitamin D concentrations (≥50 nmol/L). Higher concentrations of vitamin D were associated with lower incidence of all-cause dementia and AD (HR 0.99 (95%CI 0.98; 0.99); HR0.99 (95%CI 0.98; 0.99), respectively). In particular, subjects with vitamin D deficiency (25.3%, <25 nmol/L) were at increased risk for all-cause dementia and AD (HR1.91 (95%CI 1.30; 2.81); HR2.28 (95%CI 1.47; 3.53), respectively). Vitamins A and E and beta-carotene were unrelated to (AD) dementia. Conclusions. Vitamin D deficiency increased the risk to develop (AD) dementia. Our study supports the advice for monitoring vitamin D status in the elderly and vitamin D supplementation in those with vitamin D deficiency. We observed no relationships between the other vitamins with incident (AD) dementia, which is in line with previous observational studies.
Online veröffentlicht: 23. December 2022
Gesehen am 06.08.2024